(untitled) (El Taco en la Brea, 2019)
The issue of the subject makes reference to the impasse of the concept in contemporary philosophy, even to its elimination. There are different positions, however, that consider that it is still there, but that it is not the same subject. Without doubt, it is no longer a source of truth or guarantee of an experience, because it has ceased to be a response to diverse objects and interpellations. It is a virtual subject that does not act "for something", nor receives from something meaning or identity, and therefore is intransitive, but no less true. This essay juxtaposes Alain Badiou’s most recent publications about the subject with Philip Seymour Hoffman par exemple, the Belgian work of Rafael Spregelburd, which suggests that although the subject does not believe in its or others’ identities, they exist as fictions, a Belgian theme if there are any. If the fictions have no reference is because they are in themselves real, are part of the existing. Philip knows that a role he chooses to play is for him and holds in it itself its own purpose. An intransitive subject appears: true to his own act.